Methodology for Analysis of Microplastics in Fine Fraction of Urban Solid Waste - Katia Paola Avila-Escobedo; Karen Yazmín Moctezuma-Parra; Juan Carlos Alvarez-Zeferino; Rosa María Espinosa-Valdemar; Perla Xochitl Sotelo-Navarro; Alethia Vázquez-Morillas; Arely Areanely Cruz-Salas (Microplastics)
This study addresses the pressing need for standardized methodologies to quantify microplastics (MPs) within the fine fraction of municipal solid waste (MSW), often overlooked despite its potential environmental impact. Five extraction protocols were evaluated to identify the most effective method for isolating MPs in fine waste. These were specifically applied to samples from the Universidad Autónoma Metropolitana and one transfer station in Mexico City. A potassium hydroxide digestion protocol with subsequent flotation and centrifugation steps achieved optimal results, ensuring complete organic matter degradation and high microplastic recovery. Subsequent analyses revealed notable concentrations of MPs, primarily fragments and fibers, with higher abundance at the university site. Statistical tests confirmed significant differences between the sample sites. These findings highlight the vulnerability of MSW fine fractions to microplastic contamination and underline the importance of targeted waste management strategies. This research contributes to understanding microplastic behavior in waste management systems and emphasizes the need for mitigation efforts to prevent environmental contamination.